Association of serum adipocyte fatty acid-binding protein and apolipoprotein B /apolipoprotein A1 ratio with intima media thickness of common carotid artery in dyslipidemic patients - Orsag, Jiri; Karasek, David; Halenka, Milan; Vaverkova, Helena; Spurna, Jaromira; Kubickova, Veronika; Lukes, Jiri; Zadrazil, Josef (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2019)
BACKGROUND: Diseases caused by atherosclerosis play the most important role in mortality and morbidity worldwide. Serum adipocyte fatty acid binding protein (A-FABP) seems to be a new promising marker to determine the risk of atherosclerosis. OBJECTIVE: The aim of this study was to evaluate relationships between serum A-FABP levels in studied individuals and to assess the possibility of modeling the intima media thickness of the common carotid artery (C-IMT) using A-FABP levels and other observed characteristics. METHODS: Seventy two Caucasian individuals were enrolled and divided into 3 groups: dyslipidemic patients with or without metabolic syndrome (MetS+, n=17; MetS-, n= 34) and controls (n=21). RESULTS: There was confirmed the well-established risk profile of individuals with MetS (unfavorable lipid and lipoprotein profile, as well as increased parameters of insulin resistence and C-IMT). A-FABP concentrations in this group were significantly higher in comparison with both MetS- and controls. CONCLUSION: Using multiple linear regression models of C-IMT values for all individual data, healthy controls and dyslipidemic patients without metabolic syndrome (MetS-) A-FABP levels were not revealed as an important predictor of C-IMT in our model. In contrast, age, gender, waist circumference, nonHDL cholesterol levels and ApoB/ApoA1 ratio were important repressors of C- IMT in study individuals. This finding may be attributed to the overwhelming effect of other more robust risk factors for atherosclerosis in these individuals.
Keywords: Fatty Acid-Binding Proteins; Metabolic Syndrome; Middle Aged; mužské pohlaví; ateroskleróza; dyslipidemia; Adult; Atherosclerosis; Apolipoprotein A-I; Carotid Artery, Common; intimomediální šíře tepenné stěny; nemoci arterie carotis; apolipoprotein A-I; dyslipidemie; ženské pohlaví; Carotid Intima-Media Thickness; metabolický syndrom; Humans; apolipoprotein B-100; Apolipoprotein B-100; lidé středního věku; adipocyte fatty acid binding protein; dospělí; proteiny vázající mastné kyseliny; inzulinová rezistence; Female; Insulin Resistance; arteria carotis communis; intima media thickness; Dyslipidemias; Carotid Artery Diseases; lidé; Male